A justiça restaurativa: fundamentos ético-filosóficos - Saldanha, Renata Torri (2018)
This dissertation aims to analyze Restorative Justice and its practices, to find a meeting point for the foundation of these practices in Philosophy, especially based on the systemic-phenomenological theory of Bert Hellinger. Restorative Justice is a relatively new topic in Brazil and it has been increasingly used, but it is still needy the study of this subject when is not under a practical bias. Thus, this work seeks to conceptualize the theme based on the bibliographical review on the subject, with Kant, Hegel and Bert Hellinger. In the first chapter, the context of the flowering of restorative practices in Brazil, with a focus on the criminal area and the essentiality of its theory, is worked on: new vision of conflict, inclusion, participation, (co) responsibility, voluntariness, honesty, humility, interconnection, empowerment, hope, solidarity and the encounter. In the second chapter, Restorative Justice is approached from a critical perspective, especially on the basis of Kant and Hegel, the main framers of the current model of retributive justice.For Kant, crime is the non-fulfillment of a duty and punishment is a punishment for such an action, that is, punishment is the retribution of the evil of crime with the evil of pen, in a strictly formal paradigm. In Hegel, law is the most accurate form of law and its violation hurts the highest degree of human freedom. The Law defines the duties and the rights of the subjects. Duty is negative determination and right is positive determination of freedom. But since law and duty can be denied, law internalizes its own negation, so that this negation is not formally infinite. Thus, the denial of law by the law itself is the sanction, which also denotes a formalist bias of the concept of justice and punishment. Finally, in the last chapter, and after locating the central elements of restorative practices, we seek in Bert Hellinger's systemic-phenomenological theory a foundation for restorative practices. Bert Hellinger supposes that there are three laws that govern all human relationships: belonging, hierarchy and balance. As every system values inclusiveness, belonging is the right of everyone to be part of it. Hierarchy is the order of precedence of people as time passes. Finally, balance is the trade-off between giving and taking, representing a flow of exchange that animates human relationships. The major point of contact between restorative practices and the systemic-phenomenological theory is the change of perception in relation to the conflict, with the inclusion, which derives from the right to belong, the equality, the dignity of the human person, which makes reconciliation possible and opens the way to peace, enabling, in turn, the construction of the sense of justice. concluding that Restorative Justice is a meeting with itself and with the other, face-to-face, aiming to understand the hidden causes and entanglements which led to conflict in a larger context (beyond the conflict), with the assumption of the responsibility of each one to the event of the conflict and construction of the systemic reparation of damages (material, spiritual, emotional, transgenerational, psychological, symbolic). Bert Hellinger's theory allows us to transcend the differentiations that exclude and restore the basic human need for connection with other human beings.